2009
DOI: 10.1002/mc.20591
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor parafibromin is required for posttranscriptional processing of histone mRNA

Abstract: Parafibromin, encoded by the gene HRPT2, is a tumor suppressor protein associated with the RNA polymerase II-associated complex, Paf1 complex. HRPT2 mutations were first identified in patients with the multiple endocrine neoplasia syndrome, hyperparathyroidism-jaw tumor (HPT-JT) syndrome, and have also been found in sporadic parathyroid and renal tumors. However, the mechanisms by which parafibromin suppresses tumor formation remain unknown. In this study, we identify a novel role of parafibromin in the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 35 publications
(43 reference statements)
0
19
0
Order By: Relevance
“…Moreover, in humans the PAF1c subunit Leo1 interacts with Ranbp2, a nuclear pore complex protein (Forler et al 2004; Rozenblatt-Rosen et al 2005). Recently, Farber et al (2010) reported that Cdc73 is required for proper histone mRNA 3′ processing and export to the cytoplasm. Together, these results support the view that PAF1c may have yet an additional function, to facilitate nuclear export of the mRNAs of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in humans the PAF1c subunit Leo1 interacts with Ranbp2, a nuclear pore complex protein (Forler et al 2004; Rozenblatt-Rosen et al 2005). Recently, Farber et al (2010) reported that Cdc73 is required for proper histone mRNA 3′ processing and export to the cytoplasm. Together, these results support the view that PAF1c may have yet an additional function, to facilitate nuclear export of the mRNAs of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the multifunctional PAFc was found to be required for transcription-coupled polyadenylation stimulated by the prototypical transcriptional activator GAL4-VP16 (167). Moreover, the PAFc subunit Cdc73 is essential for proper histone mRNA 3’ processing as well as export to the cytoplasm (168). PAFc likely accomplishes these tasks through recruiting key polyadenylation factors such as the cleavage/polyadenylation specificity factor (CPSF), cleavage stimulation factor (CstF), and symplekin, a scaffolding protein for 3’ processing, to transcribing Pol II (169, 170).…”
Section: Transcription Elongation Coupled Eventsmentioning
confidence: 99%
“…(C) rkr1D (KY2309) and rkr1D sup35-Y351C (KY2306) strains were used for 10-fold dilution analysis on YPD and YPD containing 50 mM CdCl 2 and incubated at 30°for 3 days. and in altered poly(A) site utilization, which produce substrates for mRNA surveillance pathways (Mueller et al 2004;Penheiter et al 2005;Nordick et al 2008), and defects in hPaf1C give rise to aberrant transcripts, which are inefficiently processed or exported (Farber et al 2010;Nagaike et al 2011). In agreement with these earlier observations, we have shown that deletion of RTF1 results in decreased protein product from two nonstop reporters ( Figure 7), presumably because the absence of Rtf1-dependent histone modifications leads to transcriptional alterations and/ or effects on RNA export, stability, or translation.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of human Paf1C (hPaf1C) subunits impairs mRNA cleavage, polyadenylation, and export to the cytoplasm (Nagaike et al 2011). Additionally, loss of hCdc73 results in aberrantly processed and polyadenylated histone mRNAs (Farber et al 2010). In yeast, deletion of Paf1C subunits leads to decreased poly(A) tail length and alternative poly(A) site usage (Mueller et al 2004;Strawn et al 2009).…”
mentioning
confidence: 99%